Analysis of the PLN Peduli Program in the Context of Improving the Creativity and Economy of the Young Community of the Street Coffee Social Community - Gautama, Wijaya (Contemporary Journal on Business and Accounting, 2024)
Purpose – The purpose of this study is to find out how PT PLN (Persero) North Suluttenggo Distribution Main Unit manages the social and environmental responsibility program. Design/methodology/approach – This case study involved several small groups of youth in the cities of Manado, Tomohon and Bitung, North Sulawesi Province. Logical framework method through the development of the creative economy and Micro and Small Enterprise. Findings – The results of the study show that the social aspect of this program helps to increase the promotion of culinary beverages, especially coffee, in the cities of Manado, Tomohon, Bitung and its surroundings. In terms of economic aspects, this program strongly supports the economy and creativity of young people through Micro and Small Business booths that are mobile. Originality – This Research studies the development of the coffee community in Manado Keywords: Social and Environmental Responsibility, Corporate Social Responsibilities, Creative Economy, Micro and Small Enterprises, Street Coffee Paper Type Research Result